Infrared-to-visible frequency upconversion in Pr3+/Yb3+- and Er3+/Yb3+-codoped tellurite glasses - dos Santos, P. V.; Vermelho, MVD; Gouveia, E. A.; de Araujo, M. T.; Gouveia-Neto, A. S.; Cassanjes, F. C.; Ribeiro, SJL; Messaddeq, Younes [UNESP] (Elsevier B.V., 2002)
Upconversion luminescence and thermal effects in Pr3+/Yb3+- and Er3+/Yb3+-codoped 60TeO(2)-10GeO(2)-10K(2)O-10Li(2)O-10Nb(2)O(5) tellurite glasses excited by CW infrared radiation at 1.064 mum is reported. Generation of intense green and red fluorescence emission in Er3+/Yb3+-codoped samples and appreciable upconversion luminescence in the wavelength region of 450-680 nm in Pr3+/Yb3+-codoped samples is observed. Temperature-induced enhancement of X12 in the upconversion efficiency in Er3+/Yb3+- and X10 in the Pr3+/Yb3+-doped samples is demonstrated. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: luminescence; rare-earth; glass; thermal-effect; upconversion